Do Search Engines Display All Search Hits? - Ali, Mufazil; Loan, Fayaz Ahmad (Library philosophy and practice, 2021)
Purpose: The web is used to gather information through Search tools globally. These search tools display results as HITS (Hyper-Text Induced Theme Search). This study aims to explore how accurate search tools are when search hits are counted and displayed. Methodology: The paper began with search tools and search terms recognition. Academic search tools Google Scholar, BASE (Bielefeld Academic Search Engine), CORE (Connecting Repositories) were identified. Using the Dewey Decimal Classification (DDC), the subject areas were selected from the fields of Economics and Political Science. Search terms were selected from the Sears List of Subject Headings (SLSH). The searches were conducted in the simple search mode of the search engines. The total number of hits shown by search tools was recorded, and the hits were then manually counted while navigating from one page to the next to identify the true number of search hits. Findings: The findings reveal that there is a large difference in the number of hits claimed by the BASE, CORE, and Google Scholar and actual hits displayed. However, the actual hits don't vary significantly between and among search engines. Research Limitations: The study is limited to only three academic search tools. Originality/value: Few studies have been conducted to estimate the search results of search engines. However, no study has covered these three academic search engines so far.